FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI KLINIK CITRA MARINDAL KECAMATAN DELI TUA KABUPATEN DELI SERDANG TAHUN 2023 - Sitepu, Stefani Anastasia (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Colostrum is the primary liquid secreted by using the mammary glands. Introducing colostrum early and persevering with to breastfeed is the quality safety for babies because infants can avoid sickness and have 10-17 times greater antioxidants than mature milk. Delima, 2020). The purpose of this observe turned into to decide the connection between infant feeding of colostrum in 2023 on the Citra Marindal medical institution and statistics, postpartum mothers' attitudes, sources of information, social aid and schooling. that is the sort of quantitative studies. studied with the aid of cross-sectional research approach. The populace and pattern of this look at consisted of 47 children, along with forty seven youngsters accrued by purposive sampling method. The studies device is a survey. information had been analyzed using chi-squared test. The results of this take a look at show that there's a relationship between maternal understanding and colostrum with P fee (0.001), there is a dating between mother's mindset to colostrum supply P (zero.037). and the relationship among social support and colostrum. P(0.0.5), there may be a courting between statistics sources and colostrum. there is a courting P(zero.002) and a courting P(zero.002) between schooling and use of colostrum. it's been established that there may be a relationship between maternal expertise, maternal attitudes, assets of data, social guide, and training approximately colostrum. Colostrum may be given to moms who've given birth to a infant.